Architectonic spacer building system. - Ibrahim, Rahinah; Jaganathan, Siva (2009)

(untitled)
The architectonic spacer building system is a simplified prefabrication assembly using industrialised building system concept in the construction industry. Accordingly, the architectonic spacer building system for skeleton construction which used for developing design assembly for physical building components in a modular industrialised building system (IBS), characterised in that the architectonic spacer building system includes spacer having predetermined shape for use in formulate modular form of building component; wherein the spacer is a piece of physical building assembly component to integrate with various physical building components in prefabrication. The use of the spacer system can increase the degree of flexibility in obtaining multi dimensional building forms (e.g. shape) such as rectangular, square, polygon, triangle, etc. Accordingly, the spacer can be a designed principle for flexible assembly of roof such as pyramid roof, mansard roof (double slope), cone roof by using the composite key roof connector. Said spacer is a key designed assembly system that supports flexible assembly of design-integrated industrilised building system made up of pre-assembled and standardised physical building completes the assembly of industrialised components. The same spacer-designed assembly system can also be used in other engineering or industrial applications such as furniture, etc.